Availability And Utilization of ICT Facilities for Teaching, Learning, and Research: The Librarian’s Perspectives - Abule, Mudassir Abubakar (MiddleBelt Journal of Library and Information Science, 2013)
This paper examines the availability of Information and Communication Technology (ICT) facilities in the library and the use of it in enhancing teaching, learning and research in the University environment. The concept of ICT was discussed with an adaptation for this discuss. The historical development of ICT in the library was examined, while the use of library friendly software was also discussed. The use of ICT to library functions has its challenges. These challenges are identified and appropriate recommendations provided. The provision and development of ICT facilities in the library has encouraged and improved students’ usage of the library and teaching easier for lecturers as necessary references are easily found and brought to the notice of students’ users; lecturers are able to conduct research that improves their output to their students. The paper concludes that ICT has remarkably benefited university libraries efficiently in enhancing the achievements of the goals for which they are established.